Workforce Knowledge in Mining Safety Management System Policy Implementation - Komeyni Rusba; Sri Wahyuni; Nunung Nurwati (Universitas Teuku Umar, 2022)
Describe, analyze, and explain how labor knowledge in the implementation of occupational safety protection in PTLiKaKa dan PTWeMi. This study uses a qualitative approach that aims to find the depth of information naturally in a particular case and is research that generates descriptive data. The informants in this research are the general manager, the health safety and environmental manager, the human resource development manager, and two people labor. Human and natural resources, listed in the occupational safety and health management policies and work environment, are the form of company commitments. The company's commitment is a normative goal and needs to be translated into more operational service programs. Significance: Implementation and commitment are transferred into a company policy by the top management of the human resources department and occupational health and safety department. Labor assumes a commitment to implementing the policy as an effort by the company to overcome the problem of protection of occupational safety management and to promote the development of a safe work environment.